Text, Author, Context: Comparative Parallels of Shakespeare, Selimović, Hamlet, Ahmed Nuruddin, Hamlet and Death and the Dervish - Terzić, Marija S. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
This paper examines the authors William Shakespeare and Meša Selimović, their works, the play Hamlet and the novel Death and the Dervish, their heroes, Hamlet and Ahmed Nuruddin, and their coping in the socio-political and social context in which they live, through the transposition motifs from the societies in which they lived among which the murder of an innocent person for political purposes is crucial. The dominating topic of death in both the play and the novel is taken from the lives of the authors which at first glance appear to be too far apart in many aspects, making it difficult to form a connection between them. The relationship that Nietzsche finds between elements such as the author, the text, and the context, which Slobodan Grubačić speaks about in his book, is the theoretical backbone on which the resemblance between the two said authors, their mentioned masterpieces, and their protagonists is built.